Custom Foot Orthoses: A Retrospective Analysis of 1000 Prescriptions From New Zealand Podiatrists - Aaron Jackson; Kelly Sheerin; Duncan Reid; Tim Ganley; Ben Lamb; Matthew R. Carroll (Journal of Foot and Ankle Research)
ABSTRACT Background Podiatrists frequently prescribe foot orthoses to manage a range of musculoskeletal complaints. This study aimed to understand what characteristics were included in the design of custom foot orthoses, how symmetrically these were applied and whether there was an association between these features and the clinical diagnosis. Methods One thousand orthotic prescriptions were obtained from two commercial orthotic labs in New Zealand. Twenty‐six prescription characteristics were analysed. Descriptive data detailed the frequency of included characteristics. The symmetry feature was derived according to the characteristics of both feet and analysed considering the number of times the left foot differed from the right foot. Clinical diagnoses were grouped, and for the most common four (plantar heel pain, pes planus, posterior tibial tendon and ankle sprain), associations between the prescription characteristics selected and diagnosis were analysed using cross tabulations and chi‐squared tests. Results The most common prescription characteristics were a Polyamide 11 shell (80%), a shell thickness of 3 mm (54%), modified root shell style (61%) and varus cast correction (64%). Additionally, deep heel cups (36%), medial rearfoot (Kirby) skives (36%) and lateral forefoot wedges (22%) were the most prescribed modifications. Fifty‐eight percent of prescriptions were identical between the left and right sides. The most common diagnosis was plantar heel pain (11%). Plantar heel pain was associated with the characteristics of plantar fascia groove (p < 0.001), forefoot lateral wedge (p < 0.001) and heel cushion (p < 0.001). Conclusion Strong associations between orthotic design characteristics and diagnoses indicate consistency in prescription variables amongst New Zealand podiatrists when prescribing custom foot orthoses. Plantar heel pain and pes planus are the two clinical diagnoses for which podiatrists prescribe the most custom foot orthoses. The high degree of similarity and symmetry in the prescription of orthoses raises questions regarding the specificity of prescriptions and opens a potential for future research on the topic.